Novel Miscanthus Germplasm-Based Value Chains: A Life Cycle Assessment - Wagner, Moritz; Kiesel, Andreas; Hastings, Astley; Iqbal, Yasir; Lewandowski, Iris (Frontiers in Plant Science, 2017)
In recent years, considerable progress has been made in miscanthus research: improvement of management practices, breeding of new genotypes, especially for marginal conditions, and development of novel utilisation options. The purpose of the current study was a holistic analysis of the environmental performance of such novel miscanthus-based value chains. In addition, the relevance of the analysed environmental impact categories was assessed. A Life Cycle Assessment was conducted to analyse the environmental performance of the miscanthus-based value chains in 18 impact categories. In order to include the substitution of a reference product, a system expansion approach was used. In addition, a normalization step was applied. This allowed the relevance of these impact categories to be evaluated for each utilization pathway. The miscanthus was cultivated on six sites in Europe (Aberystwyth, Adana, Moscow, Potash, Stuttgart and Wageningen) and the biomass was utilized in the following six pathways: 1) small-scale combustion (heat) – chips; 2) small-scale combustion (heat) – pellets; 3) large-scale combustion (CHP) – biomass baled for transport and storage; 4) large-scale combustion (CHP) – pellets; 5) medium-scale biogas plant – ensiled miscanthus biomass; and 6) large-scale production of insulation material. Thus, in total, the environmental performance of 36 site x pathway combinations was assessed. The comparatively high normalized results of human toxicity, marine and freshwater ecotoxicity, and freshwater eutrophication indicate the relevance of these impact categories in the assessment of miscanthus-based value chains. Differences between the six sites can almost entirely be attributed to variations in biomass yield. However, the environmental performance of the utilization pathways analysed varied widely. The largest differences were shown for freshwater and marine ecotoxicity, and freshwater eutrophication. The production of insulation material had the lowest impact on the environment, with net benefits in all impact categories expect three (marine eutrophication, human toxicity, agricultural land occupation). This performance can be explained by the multiple use of the biomass, first as material and subsequently as an energy carrier, and by the substitution of an emission-intensive reference product. The results of this study emphasize the importance of assessing all environmental impacts when selecting appropriate utilization pathways.